Dissipation of post‐pulse laser‐induced alignment of CO2 through collisions with Ar. (16th January 2015) - Chaussard, F.; Vieillard, Th.; Billard, F.; Faucher, O.; Hartmann, J.‐M.; Boulet, C.; Lavorel, B.; Joubert, Pierre; Lavorel, Bruno; Kiefer, Johannes; Moger, Julian
<x xml:space="preserve">Abstract</x> In this paper, laser‐induced field‐free alignment of CO2 in mixtures with Ar is investigated under dissipative conditions (up to 15 bars) at room temperature. The degree of alignment is temporally monitored by a polarization spectroscopy technique, where a weak probe pulse measures the transient birefringence resulting from the alignment. The data are analyzed with a quantum mechanical density matrix formalism using properly J‐dependent and M‐dependent state‐to‐state transfer rates, which was previously successfully tested on pure CO2 and CO2–He mixtures. The same consistency is obtained between experiments and calculations, in particular the decay times of both the transient revivals and the permanent component of the alignment are accurately predicted by the model. Copyright © 2015 John Wiley & Sons, Ltd.